The Influence of Product Quality and Prices on Customer Satisfaction at Pt. Sources of Beautiful Works in Bogor City - Sudarijati; Titiek Tjahja Andari; Mellyinda Apriliani (International Journal of Integrated Science and Technology, 2024)
This study aims to analyze and identify the effect of product quality and price simultaneously and partially on customer satisfaction at PT Sumber Karya Indah in Bogor City. The questionnaire was distributed to 100 respondents who were taken with non-probabiliy sampling technique. The analysis method used in this research is descriptive and verification method. The results showed that product quality and price simultaneously and partially had a positive and significant effect on customer satisfaction at PT Sumber Karya Indah Bogor. The most dominant factor affecting customer satisfaction is product quality.